A study on how HRIS can be improved and made efficient for the banking Industry and Sonali Bank - Mahjabin, Maliha (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.